A combination of calcium hydroxide and sodium hydrosulphate controls pathogens causing environmental mastitis in recycled manure solids - Praveen, Selladurai; Kataktalware, Mukund A.; Meena, Priyanka; Lavanya, Maharajan; Patoliya, Priyanka; Jeyakumar, Sakthivel; Ravindra, Menon Rekha; Chauhan, Mamta; Ramesha, K. P.; Devi, G. Letha; Kastelic, John P.; Dhali, Arindam (Bioresources and bioprocessing, 2024)
Recycled manure solids (RMS) are dried cow dung processed using a manure dewatering machine and subsequently sun-dried to ~ 20% moisture. Benefits of RMS include abundant availability, low cost, and eco-friendliness, but its use as bedding material for cows is hindered by a moisture content that promotes microbial growth. This in vitro study evaluated impacts of calcium hydroxide (CH; 5 and 7.5%) and sodium hydrosulphate (SHS; 6 and 8%), independently and in combinations, at various depths of RMS, on physicochemical and microbial properties. The CH-treated groups had increased pH and reduced moisture on Day 0. Incorporating 7.5% CH + 6% SHS at 15–20 cm, and 7.5% CH + 8% SHS at all depths, effectively suppressed Escherichia coli and Klebsiella spp. Furthermore, a combination of 7.5% CH + 8% SHS at 20 cm inhibited coliform growth, whereas 7.5% CH with 6% SHS inhibited Streptococcus spp . In conclusion, a combination of 7.5% CH with either 6 or 8% SHS at a depth of 15 cm in RMS was particularly effective in controlling environmental mastitis-causing pathogens, specifically E. coli and Klebsiella spp. Graphical Abstract